Comic Learning Media "Three Friends" in the Akidah Akhlak (Moral Creed) Subject - Nasution, Awal Kurnia Putra; Rahmadani, Rina (Journal of Education Technology, 2020)
The purpose of the study was to create a valid and practical learning media comic on moral subject. The type of this research was Research and Development by using the Borg & Gall development model which was consisted of 10 steps. The data analysis technique used in this study was a quantitative descriptive analysis. The instrument used to collect data on the development of the moral comic media was a questionnaire and the trial subjects in this research were media experts, material experts, teachers and the seventh-grade students of MTs (Islamic Junior High School). Based on the validation of material experts and media experts, it showed that the results of the validation of material experts with a percentage value of 81% or very feasible and the results of the validation of media experts with a percentage value of 94.2% or very feasible. The results of trial subjects on the seventh-grade teachers as an expert practitioner got a percentage value of 97% or very feasible and the results of the trial on 10 respondents got the general percentage value of 87.6% or very good. Overall, it showed that comic media was very suitable to be used as learning media. The implication of this research was the existence of comic learning media that could be used by teachers while teaching so that the choice of learning media was varied and the learning quality got better.